PELAKSANAAN KEWENANGAN PEMERINTAHAN TERHADAP OTONOMI DESA DI DESA CARAWALI KECAMATAN WATANG PULU KABUPATEN SIDENRENG RAPPANG - Nursiah SIdi (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract This study aims to determine the implementation of government authority over village autonomy in the village Carawali District of Watang Pulu District of Sidenreng Rappang and to find out how much the exercise of government authority over village autonomy in the village of Carawali District of Watang Pulu District of Sidenreng Rappang the population in the this study is the entire population registered as comunities in Carawali village District of Watang Pulu totaing 2,207 people. The sampling techniques uses the slovin formula with the results of 96 respondents, tekan based on a random sampling technique that is a random sample of the eutire population of the communty. Data collection techniques used i this study were observation, interviews, questionnaires, and library studies. The collected data is then used by means of dat analysis, using frequency table and litert scales.The resolts of this study show the implementation of government authorty in the village Carawali District of Watng Pulu District of Sidenreng Rappang that 70% of 100% of the oxpected results, whisch is classified as good. As for the factors that influence the exrase of authority influnced by the absence of implmentation of the devision of goverment authority in the village Carawali District of Watang Pulu District of Sidenreng Rappang is 71% of 100% of the expected results which are in the good category. Keywords: Authority, Village Government, and Village Autonomy